Heat Stress-Mediated Constraints in Maize (Zea mays) Production: Challenges and Solutions - El-Sappah, Ahmed H.; Rather, Shabir A.; Wani, Shabir Hussain; Elrys, Ahmed S.; Bilal, Muhammad; Huang, Qiulan; Dar, Zahoor Ahmad; Elashtokhy, Mohamed M. A.; Soaud, Nourhan; Koul, Monika; Mir, Reyazul Rouf; Yan, Kuan; et al. (Frontiers in Plant Science, 2022)
An increase in temperature and extreme heat stress is responsible for the global reduction in maize yield. Heat stress affects the integrity of the plasma membrane functioning of mitochondria and chloroplast, which further results in the over-accumulation of reactive oxygen species. The activation of a signal cascade subsequently induces the transcription of heat shock proteins. The denaturation and accumulation of misfolded or unfolded proteins generate cell toxicity, leading to death. Therefore, developing maize cultivars with significant heat tolerance is urgently required. Despite the explored molecular mechanism underlying heat stress response in some plant species, the precise genetic engineering of maize is required to develop high heat-tolerant varieties. Several agronomic management practices, such as soil and nutrient management, plantation rate, timing, crop rotation, and irrigation, are beneficial along with the advanced molecular strategies to counter the elevated heat stress experienced by maize. This review summarizes heat stress sensing, induction of signaling cascade, symptoms, heat stress-related genes, the molecular feature of maize response, and approaches used in developing heat-tolerant maize varieties.